2004
DOI: 10.1525/eth.2004.32.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Models and Metaphors for Marriage: An Analysis of Discourse at Japanese Wedding Receptions

Abstract: This article uses metaphor analysis to delineate the cultural model of marriage expressed in speeches at Japanese wedding receptions. Wedding speakers used three main metaphors for talking about marriage: marriage as a joint creation, marriage as a physical union, and marriage as a journey. These metaphors were used to express a number of themes including the concepts that marriage is a new beginning, requires joint effort and cooperation, is ideally a lasting union, and involves love, trust, and emotional uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…These models represent the sophisticated regulatory mechanism for managing the behaviours of members of communities across a full spectrum of communal domains such as family, healthcare, education, work, governance, and many more. Using various terms (mostly “cultural models,” and “social representations”), scholars have examined the SCMs of health and healthcare (Hickman, ; Jovchelovitch & Gervais, ; Kirmayer & Sartorius, ; Kleinman, , ; Murray, Pullman, & Rodgers, ), education (DeZutter, ; Fryberg & Markus, ; Gee, ; Li, ), parenting and childrearing (Chao, ; Keller, ; Keller et al., ; Suizzo, ), romantic love (de Munck & Kronenfeld, ), marriage (Dunn, ; Quinn, ), the self (Bharati, ; Hollan, ), sex (Lavie‐Ajayi & Joffe, ), work and employment (Strauss, ), gender, work, and management (Hayes & Way, ; Hirsch, ); they have discussed models of nature (Bang, Medin, & Atran, ), the environment (Ignatow, ; Paolisso, Weeks, & Packard, ), and religion (Geertz, ; Spiro, ) along with many other models that people deal with in their daily communal lives. SCMs constitute a deep layer of the sociocultural regulation that underlies politics, economics, and law; in fact, they structure and guide the functioning of these institutions.…”
Section: The Theory Of Sociocultural Modelsmentioning
confidence: 99%
“…These models represent the sophisticated regulatory mechanism for managing the behaviours of members of communities across a full spectrum of communal domains such as family, healthcare, education, work, governance, and many more. Using various terms (mostly “cultural models,” and “social representations”), scholars have examined the SCMs of health and healthcare (Hickman, ; Jovchelovitch & Gervais, ; Kirmayer & Sartorius, ; Kleinman, , ; Murray, Pullman, & Rodgers, ), education (DeZutter, ; Fryberg & Markus, ; Gee, ; Li, ), parenting and childrearing (Chao, ; Keller, ; Keller et al., ; Suizzo, ), romantic love (de Munck & Kronenfeld, ), marriage (Dunn, ; Quinn, ), the self (Bharati, ; Hollan, ), sex (Lavie‐Ajayi & Joffe, ), work and employment (Strauss, ), gender, work, and management (Hayes & Way, ; Hirsch, ); they have discussed models of nature (Bang, Medin, & Atran, ), the environment (Ignatow, ; Paolisso, Weeks, & Packard, ), and religion (Geertz, ; Spiro, ) along with many other models that people deal with in their daily communal lives. SCMs constitute a deep layer of the sociocultural regulation that underlies politics, economics, and law; in fact, they structure and guide the functioning of these institutions.…”
Section: The Theory Of Sociocultural Modelsmentioning
confidence: 99%
“…Nevertheless, Japanese parents still seem to exert some influence over the mate choice of their children. To begin with, while most young people in Japan today insist that love is a necessary condition for marriage (Dunn, 2004;LeVine, Sato, Hashimoto, & Verma, 1995), Simmons, Vom Kolke, and Shimizu 2001) found that young people in Japan valued romantic love less positively than those in West Germany. The fact that across cultures an emphasis on romantic love tends to correlate negatively with the occurrence of arranged marriages (Williams, White, & Ekaidem, 1979), suggests that Japanese parents still influence their offspring's mate choice more than in Western cultures.…”
Section: Parental Influence In Japanmentioning
confidence: 99%
“…Guests who are asked to speak at Japanese wedding receptions draw on various formal patterns and formulaic phrases to construct their speeches within the conventionalized framework of the wedding speech genre. This includes the use of formulaic phrases to open and close the speeches (Dunn 2005a), gender-stereotypical praise of the bride and groom (Dunn 2005a), conventional metaphors for marriage (Dunn 2004), and a ceremonial speech style involving high levels of honorific language (Dunn 2005b). As with many other genres, the opening and closing sections of Japanese wedding speeches are particularly rich in generic framing devices.…”
Section: Genre or Type Interdiscursivitymentioning
confidence: 99%
“…Such metaphors were particularly common at the end of speeches when speakers offered wishes or requests for the couple's future married life. For example, couples were often urged to cooperate together to build a new home: In addition to this image of "building a home together," other common metaphors included images of marriage as a union or a journey through life together (Dunn 2004). The trope of "building a home" and other conventional metaphors function as textually discontinuous speech formulas that allow the insertion of appropriate adverbial or adjectival phrases.…”
Section: Figurementioning
confidence: 99%